Improving Collaboration between Mechanical, Electrical, and Software Engineers during the Early Stage Design Process in Embedded Systems Suppliers - Dvoryankov, Eugene (My University, 2025)
The increasing reliance on software in embedded systems has created new challenges for suppliers that traditionally focused on mechanical and electrical domains. In this thesis, collaboration between mechanical, electrical, and software engineers during the early-stage design process was analysed using a qualitative case study at Volvo Penta. 15 semi-structured interviews were conducted with engineers, architects, project managers, and leaders from five Volvo Group companies. Thematic analysis was applied to identify recurring patterns and challenges. 17 subthemes were generated and organised using BAPO model, under 4 main themes: Business, Architecture, Process, Organisation. Relations between these subthemes were analysed though BAPO framework. It was found that early alignment can be strengthened by new platform architecture, a new rule-based configuration tool that follows Model Based Systems Engineering practices and re-organisation to create a new unified role for a person to coordinate Mechanical, Electrical and Software disciplines. The results contribute to research on socio-technical alignment in embedded systems by combining perspectives from Model-Based Systems Engineering, Set-Based Concurrent Engineering, variability management, and the BAPO framework.
Keywords: Embedded systems; Cross-disciplinary collaboration; Early-stage design; Configuration management; Model-Based Systems Engineering (MBSE); Set-Based Concurrent Engineering (SBCE); Variability management; BAPO framework